The molecular components of phospho and glycolipid metabolism in plant cell membranes under the phosphorus deficiency - Svietlova, N.B. (Вiopolymers and Cell, 2012)
One of the aspects of molecular regulation of phosphorus metabolism in plants, the lipid components of membrane structures, has been reviewed. The refocusing of phosphoand glycolipid metabolism is an indicator of phosphorus accessibility in plants. The compensatory mechanisms of substitution of phospholipids with non-phosphorus containing glycolipids in membranes, allow plants to adapt to the phosphate (Pi) starvation. Phospholipids are the reserve pool of cellular phosphorus at reutilization of ions in the donor-acceptor system of plants. The mechanisms of transcriptional regulation of genes involved in the synthesis of phospholipids and glycolipids under Pi deficit have been analyzed.